Perception of rural adolescents and parents regarding child marriage: Findings of a community-based cross-sectional study in Bangladesh - Md. Ziaul Islam; S. M. Sharf-ul-alam; Farjana Farha; Nargis Sultana; Ananya Adhya; Sharmin Farjana (PLoS ONE, 2025)
Background Child marriage is a blazing global issue influenced by gender inequity, poverty, social norms, and insecurity. It has disastrous social, economic, and health-related consequences. Bangladesh ranks among the top ten countries in terms of child marriage, and rural girls are the most vulnerable group to it. Our study aimed to assess and compare the perception of rural adolescents and parents regarding child marriage, as well as focusing on the key factors governing such perception of the participants. Methods This community-based cross-sectional study randomly selected four unions of Dhamrai upazila (Sub-district) under the Dhaka district as study areas. The study recruited 1030 participants (515 adolescents and 515 parents) from 515 rural households using a systematic random sampling method and specific selection criteria. Data enumerators collected data through face-to-face interviews using a pretested semi-structured questionnaire and obtained informed written consent from parents and assent from adolescents. The study assessed perception related to child marriage by 25 statements formulated based on expert opinions. These statements were further organized into four domains- social, economic, psychological, and environmental through thematic analysis. We categorized the perception as “support” and “do not support” child marriage using a scoring system ranging from 0 to 25, based on the responses to 25 statements by a two-level Likert scale. Participants who obtained scores of ≥80% were considered not to support child marriage. Results The current study revealed that 25.8% of adolescents and 27.0% of parents supported child marriage. Participants lacking formal schooling were 3 times (AOR 3.00; 95% CI 1.27–7.09, p = 0.01) and participants with primary level education were 2.69 times (AOR 2.69; 95% CI 1.27–7.09, p = 0.01) more likely to support child marriage compared to participants with at least higher secondary level of education. Parents and adolescents did not differ significantly (p < 0.05) in total and domain-specific perception scores. However, substantial differences existed in various statements across the domains, and maximum disagreement was found in the environmental domain. Conclusion Supportive perception toward child marriage still exists in rural Bangladesh, and it is more prevalent among people with less or no formal education. Despite exceptions, both groups had overall similar perceptions regarding child marriage. Exploration of factors favoring support for child marriage and designing educational as well as community-based interventions specific and suitable to adolescents and parents is crucial to improve perception regarding child marriage.